PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA PERAWAT PADA RUMAH SAKIT ANNA, PEKAYON-BEKASI - Putri Sriwulan Ramadhany; Rasmansyah (Jurnal Manajemen Bisnis Krisnadwipayana, 2017)
Leadership style and compensation are the factors that are very important in improving employee performance in a company. The purpose of this study is to determine whether the style of leadership and compensation simultaneously or partially can affect the performance of nurses at Anna Hospital. The method of analysis used in this study is multiple linear regression analysis using SPSS program. The results showed that both simultaneous and partial leadership style and compensation have a positive and significant effect on the performance of nurses. This shows that a good leader who is able to provide direction and motivation to subordinates to achieve the goals set by the company can affect performance improvement as well as the fair compensation provided by the company will increase the productivity of work on every employee to be able to works optimally. Kata Kunci: Gaya Kepemimpinan, Kompensasi dan Kinerja